Hearing Loss Situation and Factors Influencing Hearing Loss among Food Processing Workers in Wiang Pa Pao district, Chiang Rai Province - Suanmuang, Maneerat; Khamthan, Phatanit; Choyae, Aree (Journal of Health Sciences and Wellness, 2024)
Hearing loss is a highly debilitating condition that significantly impacts daily activities, including work and communication-dependent tasks such as studying. Its prevalence increases each year. This study a Cross-sectional descriptive study. The objective of this study was to determine the prevalence of hearing loss and factors that influence hearing loss among 130 food processing workers in Wiang Pa Pao District, Chiang Rai Province. Data were collected by using general questionnaire and Audiometer SIBELSOUND 400 – AM. Statistical analyses utilized descriptive statistics, such as percentages, means, standard deviations, and logistic regression analysis, including odds ratios. Hearing capacity was evaluated based on the criterion that hearing loss commences when the ability to hear sounds at a volume level above 25 decibels (dB) is compromised. The results of the study found that the majority of employees started hearing impairment 68 worker (52.30%). The results of factors influence to the hearing loss of employees, including: age range 31-40 yr. (OR adj = 0.040 95% CI = 0.004-0.366), age range 41-50 yr. (OR adj = 0.068 95% CI = 0.009-0.502), age over 50 yr. (OR adj = 0.099 95% CI = 0.014-0.704) and more than 15 years of work experience (OR adj = 6.437 95% CI = 1.196-34.635). Based on the research outcomes, it is recommended to provide training to employees on preventing hazards related to loud noises and promoting the use of personal protective equipment, especially for those with extensive work experience.